Comparative computational genomic analysis between wild and domesticated species of cacao and coffee (Journal of Pharmaceutical Negative Results, 2022)
Cacao and coffee are two tropical crops with an essential annual turnover. Alkaloid products like caffeine and theobromine show that these two species share related pathways in alkaloid metabolism. Genomic proteins of three coffee species, including Coffea arabica, C. canephora and C. eugenioides, and two cacao species, Theobroma cacao, and Herrania umbratica, were compared and analyzed based on protein clustering and GO terminology. A comparison of all five species showed orthologous proteins involved in stress, disease response, alkaloid biosynthesis, regulation and transport. Based on GO terms of orthologous proteins of 5 species, two proteins, including Tryptophan decarboxylase TDC2 and Perakine reductase, were disclosed that are involved in the biosynthesis of monoterpenoid indole alkaloids. In addition, enzymes including Caffeic acid 3-O-methyltransferase, Caffeoylshikimate esterase, Caffeoyl-CoA 3-O-methyltransferase and Fatty alcohol:caffeoyl-CoA acyltransferase were found as orthologous proteins of all five studied species. Proteins of H. umbratica and C. eugenioides were asymmetrically shared with other species as their proteins were not aligned with species of coffee for H. umbratica and species of cacao for C. eugenioides. Single-copy proteins common between 5 studied species showed functions related to growth and development, stress response, phytohormones, gene expression regulation and metabolite biosynthesis. Two proteins, including Vinorine synthase and Deacetoxyvindoline 4-hydroxylase (D4H), involved in indole alkaloid biosynthesis were found as single-copy proteins among five species. These results showed biological processes and molecular functions of proteins among cacao and coffee species. Wild species of cacao and coffee are valuable genetic resources for selection and breeding.